Subcutaneous suppressive antibiotic therapy for bone and joint infections: safety and outcome in a cohort of 10 patients. (10th April 2019) - Pouderoux, Cécile; Becker, Agathe; Goutelle, Sylvain; Lustig, Sébastien; Triffault-Fillit, Claire; Daoud, Fatiha; Fessy, Michel Henry; Cohen, Sabine; Laurent, Frédéric; Chidiac, Christian; Valour, Florent; Ferry, Tristan; et al.
Abstract: Background: Optimal treatment of prosthetic joint infection and chronic osteomyelitis consists of surgical removal of biofilm-embedded bacteria, followed by a 6–12 week course of antimicrobial therapy. However, when optimal surgery is not feasible, oral prolonged suppressive antibiotic therapy (PSAT) is recommended to prevent prosthesis loosening and/or relapse of infection. Since 2010, we have used infection salvage therapy using off-label subcutaneous (sc) injection of a β-lactam as PSAT for patients in whom oral PSAT is not possible. Methods: A single-centre prospective cohort study (2010–18) reporting treatment modalities, efficacy and safety in all patients receiving sc PSAT. NCT03403608. Results: The 10 included patients (median age 79 years) had polymicrobial ( n = 5) or MDR bacterial ( n = 4) prosthetic joint infection (knee, n = 4; hip, n = 3) or chronic osteomyelitis ( n = 3). After initial intensive therapy, seven patients received ertapenem, three patients received ceftriaxone and one patient received ceftazidime by sc injection (one patient received 8 days of ceftriaxone before receiving ertapenem). In one patient, sc PSAT failed with recurrent signs of infection under treatment. In three patients, sc PSAT had to be discontinued due to side effects; in only one of these was the sc route implicated (skin necrosis following direct sc injection and not gravity infusion). Median treatment duration was 433 days. In six patients, sc PSAT was successful with favourable outcome at the time of writing. Interestingly, three patients with MDR bacterial carriage at baseline lost this under PSAT during follow-up. Conclusions: As salvage therapy, sc PSAT delivered by gravity infusion is a safe and interesting alternative when an optimal surgical strategy is not feasible and no oral treatment is available.